The genetic basis of dystonia - Warner, Tom (Henry Stewart Talks, 2014)
Dystonia outline and historical summary, Clinical characteristics, aetiology and classification of dystonia, Different dystonia phenotypes their related genes and mutations, Molecular pathogenesis and mechanisms in cellular processes and organelles, Dystonia proteins in pre- and post-synaptic areas